Determination of the teaching methodology applied for reading comprehension development of 10th graders at "Cesar Andrade Cordero School". - Flores Cabrera, Karla Estefanía (2017)
The following research study centers its attention on the reading skill is a basis to develop various abilities such as vocabulary increase; reading comprehension and even self – questioning can be developed. So, reading is a valuable skill, this study will concentrate on this ability. This research is focused on the study of reading comprehension rate in the school “César Andrade Cordero” in 10th grade students afternoon shift. This study is done to provide an analysis of the reading comprehension strategies implemented by the teacher of 10th grade. It was analyzed the English textbook and the exploration of reading exercises. The detected failure is the low English level from students, the high level presented in the English textbook, and the lack of adequate teaching methodology. Finally, it was proposed a plan to apply reading components in the three phase approach.